Efficacy of leeching (Ta‘līq al-‘Alaq) in patients with vitiligo (baras): a comprehensive case study - Iqbal, Arsheed; Rashid, Adil; Jan, Afroza; ., Haider (International Journal of Basic & Clinical Pharmacology, 2021)
Vitiligo is a hypomelanotic skin disorder in white patches appear on the skin surface and also involve the hair. The disease is idiopathic, acquired and effects 1-4 percent of the world population. It is belived that there is immunologic influence in the pathogenesis of vitiligo and there is evidence of early cell death in vitiligo melanocytes related to their increased sensitivity to oxidative stress. In Ayurveda the vitiation of three doshas results deraignment of rasa, rakta, mamsa and medadhuta which results in vitiligo patches on skin. In Unani System of Medicine (USM) the deraignment of body humours result in the Fasad-e-Ikhlat which results in the Baras (vitiligo). Since both in Ayurveda and USM leech has been used for various dermatalogicalailments including vitiligo. In this study leeching (hirudotherapy) were done in vitiligo patients of both sexes with single and multiple patches and successful results were observed.